2010
DOI: 10.1021/ja910900p
|View full text |Cite
|
Sign up to set email alerts
|

Auxiliary-Assisted Palladium-Catalyzed Arylation and Alkylation of sp2 and sp3 Carbon−Hydrogen Bonds

Abstract: We have developed a method for auxiliary-directed, palladium-catalyzed β-arylation and alkylation of sp 3 and sp 2 C-H bonds in carboxylic acid derivatives. The method employs a carboxylic acid 2-methylthioaniline-or 8-aminoquinoline amide substrate, aryl or alkyl iodide coupling partner, palladium acetate catalyst, and an inorganic base. By employing 2-methylthioaniline auxiliary, selective monoarylation of primary sp 3 C-H bonds can be achieved. If arylation of secondary sp 3 C-H bonds is desired, 8-aminoqui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
341
1
19

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 865 publications
(369 citation statements)
references
References 81 publications
8
341
1
19
Order By: Relevance
“…Among the phosphine ligands screened, 1,2-bis(diphenylphosphino)benzene (dppbz) gave the best result. The reaction tolerated various functional groups, such as terminal alkenes (55), esters (56), cyano groups (57), and trifluoromethyl groups (58). It was found that alkyl iodides could be replaced with alkyl bromides with the addition of CsI, as in 55-57.…”
Section: C-s Bond Formationmentioning
confidence: 99%
“…Among the phosphine ligands screened, 1,2-bis(diphenylphosphino)benzene (dppbz) gave the best result. The reaction tolerated various functional groups, such as terminal alkenes (55), esters (56), cyano groups (57), and trifluoromethyl groups (58). It was found that alkyl iodides could be replaced with alkyl bromides with the addition of CsI, as in 55-57.…”
Section: C-s Bond Formationmentioning
confidence: 99%
“…Dessen ungeachtet kann eine dirigierende Gruppe in situ gebildet werden, um die Notwendigkeit der Vorfunktionalisierung des Amins vor dem Schritt der C-H-Aktivierung zu umgehen. Ge, [45] Dong [46] und Yu [47] [49] Tobisu und Chatani, [50] Chen [51] bzw.R ao [52] entwickelt. Die Geometrie des Vinyliodids 110 bleibt in Chens System zur Alkenylierung des Amids 109 erhalten.…”
Section: Amine (Sulfonamide)unclassified
“…[135] Wegweisende Untersuchungen zu photochemischen Umwandlungen tertiärer Amine [136] inspirierten Yoshimitsu et al, eine C-H-Carbamoylierungsreaktion zu entwickeln und auf die Synthese von Kainsäure anzuwenden (273; Schema 54). [137] [141] als chelatisierende Einheit entscheidend. Nach der Epimerisierung des C1-Chiralitätszentrums in 276 führte die zweite C(sp 3 )-HArylierung mit 4-Iod-1,2-dimethoxybenzol (277) unter ähn-lichen Bedingungen vçllig stereoselektiv zum Kupplungsprodukt 278.…”
Section: Funktionalisierung Von C(sp 3 )-H-bindungenunclassified